Tourism development in rural areas: assessing the qualities of place in the village of Nawgoul, Iran - Hooshmand , Alizadeh; Mohamad Rasouly, Mohamad Rasouly (2008)
In developing countries, rural areas generally suffer high level of poverty, and are also characterized by lower levels of non-farm economic activity, infrastructural development, and access to essential services. As Robert & Hall (2001) say, to cope with these problems it is necessary to diversified range of rural products. Tourism is recognized as prime contributor to this process as an effective catalyst of rural socio-economic development and regeneration. Considering this point, this study assesses the qualities of place in Nawgoul as case study, a village in west of Kurdistan province, Iran. This has been dealt through document analysis, questionnaire for both residences and visitors and observation of the built form of the village and its natural setting (taking photograph and analytical drawings). Following this stage, SWOT Analysis has been used to explore strategies for decision-making, and in so doing, diversifying tourism products and therefore expanding tourism benefits to the residents. The SWOT analysis is followed by possible policy implications and executive decisions (actions) for each of the SWOT factors, which can influence the level of tourism development. The outcome of the case study is that Nawgoul and its region has the potential for nature and culture-based tourism development, but this has not been explored as of yet.